Assessing feasibility and effects of personalized remote advisories based on smartphone pictures: A formative evaluation in India - Ceballos, Francisco; Kannan, Samyuktha; Kramer, Berber (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This paper provides a formative evaluation of picture-based advisories (PBA), using a cluster randomized trial in the states of Punjab and Haryana in northern India. The study randomly assigned 203 villages to one of three treatment arms: a control group, in which farmers received generic agricultural advisories; a PBA treatment arm, in which farmers received not only generic advisories but also PBA messages personalized based on smartphone images of their crops; and a treatment arm in which farmers received picture-based insurance (PBI) coverage for visible damage to insured crops in addition to the generic and PBA messages. We find high participation among all groups of farmers, regardless of potential digital divides, indicating feasibility of an inclusive PBA approach. Moreover, PBA improved farmers’ knowledge around good agricultural practices. Although this did not translate into increased adoption of recommended practices in the short run, farmers do report that the advisory service helps them reduce risk, providing a business case for bundling this service with insurance.